Effects of Drift, Selection and Gene Flow on Immune Genes in Prairie Grouse - (:unkn) unknown (My University, 2016)
Fragmentation of natural habitats is related to population decline in many species. The resulting small and isolated populations are expected to lose genetic variation at a rapid rate, which reduces the ability to adapt to environmental change. One concern is that small populations are more susceptible to emerging pathogens due to the loss of variation at immune genes. My dissertation examined the relative effects of gene flow, genetic drift and selection on immune genes in prairie-chickens (Tympanuchus cupido), a species that has undergone drastic population declines across their range. In the first chapter, I examined how artificial gene flow through translocations of birds from Minnesota to the threatened Wisconsin population influenced genetic diversity at both neutral loci and immune genes. My second chapter explored how selection and drift shaped variation at two different functional categories of immune genes across prairie-chicken populations, including the critically endangered Attwater’s prairie-chicken (T.c. attwateri). My third chapter assessed how immune gene variation in captive-bred Attwater’s prairie-chickens is related to their immune response and survival in the wild. Overall, this dissertation provides a better understanding of how evolutionary mechanisms are shaping variation at immune genes in threatened species at both the population and individual level.
Keywords: Captive Breeding; Genetic Drift; Major Histocompatibility Complex; Population Genetics; Selection; Translocation